Los yagua en el contexto del turismo étnico. La construcción de la cultura para el consumo en el caso de Nuevo Perú - Chaparro Ortiz de Zevallos, Anahí (2008)
This article analyses the way in which culture is produced as a consumer good within the ‘ethnical tourism’, in the case of the community ‘Nuevo Perú’, in the Peruvian Amazon. It points out that tourism should be analyzed as a contemporary ritual, a social practice in itself where a new culture for a specific audience is formed. The article’s main focus consists in analyzing how culture is created for touristic purposes from the interaction between the three actors involved in the mis en scène —the tourists, the enterprise and the local population—, while at the same this interaction is placed within the global ideas that circulate around tourism and the place of destination.